A Double-Blind, Placebo-Controlled Trial to Assess Safety and Tolerability of (Thetanix) Bacteroides thetaiotaomicron in Adolescent Crohn's Disease. Issue 1 (18th January 2021) - Hansen, Richard; Sanderson, Ian R.; Muhammed, Rafeeq; Allen, Stephen; Tzivinikos, Christos; Henderson, Paul; Gervais, Lisa; Jeffery, Ian B.; Mullins, David P.; O'Herlihy, Eileen A.; Weinberg, John D.; Kitson, Geoff; et al.
Abstract : INTRODUCTION: Thetanix (gastroresistant capsules containing lyophilized Bacteroides thetaiotaomicron ) is a live biotherapeutic, under development for Crohn's disease, that antagonizes transcription factor nuclear factor kappa B, reducing proinflammatory cytokines, particularly tumor necrosis factor alpha. We aimed to assess safety and tolerability in adolescents with Crohn's disease in remission. METHODS: Subjects who were 16–18 years with Crohn's in remission (weighted pediatric Crohn's disease activity index <12.5) were recruited. Each active dose comprised ∼10 8.2±1.4 colony forming units of B. thetaiotaomicron (randomized 4:1 active:placebo). Part A was single dose. Part B involved 7.5 days twice daily dosing. Serial stools were analyzed for calprotectin, 16S rRNA sequencing, and B. thetaiotaomicron real-time polymerase chain reaction. Bloods were taken serially. Subjects reported adverse events and recorded temperature twice daily. RESULTS: Fifteen subjects were treated—8 in part A (75% men, median 17.1 years) and 10 in part B, including 3 from part A (80% men, median 17.1 years); all 18 completed. Seventy percent took concurrent immunosuppression. Reported compliance was >99% in part B. Two subjects reported adverse events deemed related—one in part A with eructation, flatulence, and reflux; one in part B with dizziness, abdominal pain, and headache. No serious adverse events were reported. There was no significant change in median calprotectin across part B (87.8 [4.4–447] to 50.5 [5.3–572], P = 0.44 by the Fisher exact test in the active group). No significant differences were found in microbiota profiles, but diversity seemed to increase in treated subjects. DISCUSSION: Thetanix, after single and multiple doses, was well tolerated. Although the numbers in this study were small, the safety profile seems good. Future studies should explore efficacy.